A novel capsule by poly (ethylene glycol) granulation for self-healing concrete - Feng, Jianhang (2021)
Minerals can be incorporated in concrete to promote self-healing. Encapsulation of minerals is needed for avoiding undesired reactions before concrete cracks. Therefore, this study designed a novel capsule. The core materials of the capsules were either cement or a combination of cement and superabsorbent polymers (SAPs), which were granulated by poly (ethylene glycol) followed by a waterproof layer (i.e., epoxy resin and sand). The structure and hydration process of capsules, self-healing efficiency of cracked mortars and healing product were characterized. Results showed that core materials in capsules could react with water with dissolution of PEG and swelling of SAP swelled in cracks. Moreover, specimens incorporated capsules showed high sealing ratio for cracks below 400 μm and even inside cracks wider than 200 μm could be bridged due to capsules with SAP. Recovery of water tightness, flexural and compressive strength were obtained. The healing products were C-S-H and CaCO₃.